2016
DOI: 10.1111/sode.12198
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Children's Church‐Based Social Support: Development and Initial Validation of the Kids’ Church Survey

Abstract: Given the importance of considering context in development, the goal of the present study was to develop and provide initial validity evidence for the Kids’ Church Survey (KCS), a new measure of children's church‐based social support. Data were collected from 1253 children ages 6–14 attending mainline Protestant, evangelical Protestant, and Catholic churches. Parallel and exploratory factor analyses supported a three‐factor solution: received (emotional) church support, perceived church support from peers, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Finally, consistent with research on the value of relationships in church for children's religiosity and spirituality (Crosby, Smith, & Frederick, 2015;Crosby & Smith, 2016) this present study showed that perceived relatedness in church was a significant predictor of children's relationship with God. The finding that perceived relatedness in church predicts relationship with God aligns with literature that reveals the value of relationships for helping individuals make meaning from religious experiences (Crosby, Smith, & Frederick, 2015;Krause & Ellison, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Finally, consistent with research on the value of relationships in church for children's religiosity and spirituality (Crosby, Smith, & Frederick, 2015;Crosby & Smith, 2016) this present study showed that perceived relatedness in church was a significant predictor of children's relationship with God. The finding that perceived relatedness in church predicts relationship with God aligns with literature that reveals the value of relationships for helping individuals make meaning from religious experiences (Crosby, Smith, & Frederick, 2015;Krause & Ellison, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…This view of an attentive and close God could be representative of "an internalization of the religious teachings of their parents and church leaders" (Crosby & Smith, 2015, p. 251). Furthermore, Crosby and Smith (2016) confirmed that children's received support from adults and connectedness with adults at church positively correlated with a view of God as supportive and caring.…”
Section: Relatednessmentioning
confidence: 61%
See 3 more Smart Citations